Gender identity and women's supply of labor and non-market work: panel data evidence for Germany - Wieber, Anna; Holst, Elke (Bonn, 2015)
"This paper aims to verify results of the innovative study on gender identity for the USA by Bertrand et al. (2015) for Germany. They found that women who would earn more than their husbands distort their labor market outcome in order not to violate traditional gender identity norms. Using data from the German Socio-economic Panel Study we also find that the distribution of the share of income earned by the wife exhibits a sharp drop to the right of the half, where the wife's income exceeds the husband's income. The results of the fixed effects regression confirm that gender identity has an impact on the labor supply of full time working women, but only in Western Germany. We also show that gender identity affects the supply of housework but in contrast to the US where women increase their contribution to non-market work when they actually have a higher income than their husbands, we find for Germany that women only barely reduce their weekly hours of non-market work once their income exceeds that of their husbands."